Ecological responsibility of Benedictine monasteries: a study of three cases (Plankstetten, Andechs and Gut Aich) - Bernard Sawicki (Polonia Sacra, 2017)
This paper presents the practical contribution of three Benedictine monasteries to an integrated ecology, strongly recommended in pope Francis’ encyclical Laudato si’. Based mainly on the materials inserted on the websites of these monasteries, a particular and important connection is observed between modern, ecological solutions and pastoral activities. Everything arises from the balanced Benedictine spirituality, where liturgy and communal life are integrated through personal prayer and reading of the Bible. After considering the motivations presented by these three monasteries for their ecological accomplishments, the specific domains are examined, such as self-sufficiency, energy and gardens.